Implementasi Simple Additive Weighting Penentuan Prioritas Penanganan Sumber Air Bersih - Evi Yulianingsih; Nia Oktaviani; Usman Ependi (ISB Atma Luhur, 2020)
Clean water is the need of every human being, for that the necessity of clean water is a priority for the government in providing services. The current problem is the lack of clean water that has not been evenly distributed due to government limitations. For that reason, in providing services, it must be according to priority in order to have a broad impact on the community. For this reason, in this research the development of an information system can be used to assist in determining priorities in handling clean water sources. In the development process the waterfall method is used while the determination of priorities uses simple additive weighting. The results showed that the simple additive weighting method can provide a clear value in determining the priority of clean water handling. This condition can be seen from the existing process in the information system, which starts from weighting, filling the survey value to simple additive weighting calculations. besides that, the information system can run well in accordance with the expected proven by the results of testing using black box testing to get the test results received